Effects of Non‐Ionic Surfactants on the Rheological, Electrical and Electrochemical Properties of Highly Loaded Silicon Suspension Electrodes for Semi‐Solid Flow Batteries. Issue 17 (1st September 2020) - Wu, Yuanyuan; Cao, Defu; Bai, Xiaojie; Liu, Hao; Hao, Huiying; Xing, Jie; Dong, Jingjing; Liao, Libing
Abstract: Silicon‐based suspension electrodes represent one of the most promising candidates as negolyte to replace lithium metal for high energy density semi‐solid flow batteries (SSFBs). Nevertheless, it remains a critical challenge to obtain Si‐based negolyte with highly loaded active material and low viscosity, which are essential for its practical application. Here, the effects of two common non‐ionic surfactants – polyvinylpyrrolidone (PVP) and Triton X‐100 (TX‐100) – on rheological, electrical and electrochemical properties of highly loaded Si (30 vol % Si) negolyte were systemically studied. It was found that the viscosity is effectively decreased by introducing steric and/or depletion interactions when adding a certain amount of non‐ionic surfactant polyvinylpyrrolidone (PVP), while good electrochemical performance of the Si negolyte was maintained. An optimal Si negolyte (adding 0.4 wt % PVP) with a low viscosity of 240 mPa s at a shear rate of 40 s −1 (i. e. about five times lower than the PVP‐free suspension) exhibits a high reversible capacity (ca. 1300 mAh/g) and stable cycling performance (>100 cycles) with a high coulombic efficiency (>98 %). In contrast, TX‐100 can react with lithium salt in the electrolyte and is not suitable to decrease the viscosity of Si negolyte. The highly loaded Si negolyte with low viscosity reported in the present work is promising for practical high energy density lithium‐free SSFBs. Abstract : Beyond the sticking point : The microstructure of the electrode paste is regulated. The conductivity and viscosity of the semi‐solid lithium‐ion liquid flow battery electrode paste are restricted by adding non‐ionic surfactant. Low viscosity and good electrochemical cycling stability are obtained by adding a certain amount of nonionic surfactant.